BIOMASSA DAN SIMPANAN KARBON PADA EKOSISTEM PADANG LAMUN DI WILAYAH NUSA LEMBONGAN - Dwikasari, Ida Ayu Indira; Arthana, I Wayan; Watiniasih, Ni Luh (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 1 (2024), 2024)
The Seagrass ecosystem is one of the important ecosystems in the ocean in mitigating global warming. This research aims to examine the potential for storing carbon stocks in seagrass biomass. The purposive sampling method was used at three location points. At each location, there are 9 quadrants for a total of 27 quadrants. The types of seagrass found were Thalassia hemprichii, Cymodocea rotundata, Enhalus acoroides, Halodule uninervis, Halophila ovalis, Halodule pinifolia with moderate diversity and moderate community stability. Seagrass conditions are relatively protected between the coast and coral reefs with the highest average density of 225 ind/m 2 . The type of seagrass with the highest density is Thalassia hemprichii. The types of substrates are sand, coral rubble, and sandy mud. The carbon stock in the Lembongan Beach area has an area of ??89.46 hectares of seagrass beds. Around 56.32% or 3,21 tons of carbon were stored as the bottom carbon stock of the substrate and 43.67% or 2,49 tons of carbon were stored as the top carbon stock of the substrate. Keywords: Thalassia Hemprichii, Seagrass, Substate, Global Warming